2007
DOI: 10.1111/j.1547-5069.2007.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Variation of Physical Restraint Use in Acute Care Settings in the US

Abstract: Wide rate variation indicates the need to examine administratively mediated variables and the promotion of unit-based improvement efforts. Anesthetic and sedation practices have contributed to high variation in ICU PR rates. Determining the types of units to target to achieve improvements in care of older adults requires study of PR sequelae rate by unit type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
151
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(159 citation statements)
references
References 28 publications
(32 reference statements)
5
151
1
2
Order By: Relevance
“…Conversely, the rate of using of PR is different based on patients' age category. For instance, patients were restrained at rates of 6% to 13%, while patients aged 65 years or older were restrained at a higher rate (18% to 22%) [3]. Similarly, Tinetti et al [7] found patients' characteristics such as disorientation, dependence on getting dressed and the use of antidepressants to be independently associated to rate of using restraints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the rate of using of PR is different based on patients' age category. For instance, patients were restrained at rates of 6% to 13%, while patients aged 65 years or older were restrained at a higher rate (18% to 22%) [3]. Similarly, Tinetti et al [7] found patients' characteristics such as disorientation, dependence on getting dressed and the use of antidepressants to be independently associated to rate of using restraints.…”
Section: Introductionmentioning
confidence: 99%
“…PRs are used in intensive care units (ICU) rather than other wards due to confusion and agitation of the patients that affect on their safety and risk for falling in the ICU [3]. In addition, a recent study reported major reasons for restraints includes "Behavioural/confused/violent" (65%) and preventing falls (62%) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The scope of the use of physical restraint is still unclear; however; frequencies between 0% and 100% have been reported. 2,[10][11][12][13] In previous studies, 2,10 the frequency of physical restraint was estimated by using surveys, a method that may be subject to bias. In observational studies [11][12][13][14] in which patients were individually examined, few different centers or ICUs were included.…”
mentioning
confidence: 99%
“…2,[10][11][12][13] In previous studies, 2,10 the frequency of physical restraint was estimated by using surveys, a method that may be subject to bias. In observational studies [11][12][13][14] in which patients were individually examined, few different centers or ICUs were included. A recent French investigation 10 indicated that in 82% of ICUs, physical restraint was used at least once during mechanical ventilation in more than 50% of the patients.…”
mentioning
confidence: 99%
“…The few studies about their use in hospitals indicate prevalence rates ranging from 3.4% to 18.5%, with restraints applied more frequently on adults aged 65 or older [4]. To search for reports on the prevalence of physical restraint use in rehabilitation settings, a literature search was conducted.…”
Section: Introductionmentioning
confidence: 99%